2009
DOI: 10.1139/x08-156
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nursery substrate and fertilization on the growth and ectomycorrhizal status of containerized and outplanted seedlings of Picea abies

Abstract: Raulí (Nothofagus nervosa) is a highly valuable and fast growing Chilean native tree species, therefore being of great interest for the establishment of plantations. The success of plantations depends upon several factors, among which nursery management can be decisive. This study evaluated the effects of slow release fertilization (FLC) in doses of 2.5, 5.0 and 7.5 kg m-3 , and of topping (with and without) on the survival and growth of raulí in a plantation with restoration purposes in the Valdivian Andes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 35 publications
3
20
1
2
Order By: Relevance
“…Results of those studies suggest that A. byssoides is an efficient root coloniser of P. abies seedlings. Its common occurrence in newly established forest plantations (Kranabetter J 2004, Menkis et al 2007, Vaario et al 2009), and better survival of abundantly colonised CR seedlings of the present study further suggest that A. byssoides may play an important role in seedlings survival and establishment following their outplanting. In support to this, Jones et al (2009) showed that 15 N accumulation in shoots and roots of spruce seedlings colonised by A. byssoides was respectively moderate and high compared to the seedlings colonised by other ECMs.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Results of those studies suggest that A. byssoides is an efficient root coloniser of P. abies seedlings. Its common occurrence in newly established forest plantations (Kranabetter J 2004, Menkis et al 2007, Vaario et al 2009), and better survival of abundantly colonised CR seedlings of the present study further suggest that A. byssoides may play an important role in seedlings survival and establishment following their outplanting. In support to this, Jones et al (2009) showed that 15 N accumulation in shoots and roots of spruce seedlings colonised by A. byssoides was respectively moderate and high compared to the seedlings colonised by other ECMs.…”
Section: Discussionsupporting
confidence: 67%
“…In a related Finnish study, Vaario et al (2009) reported that containerised P. abies seedlings grown in a similar substrate and with similar mycorrhization levels as CR seedlings, although produced satisfactory shoot growth in the nursery showed reduced growth rates after transfer to the field. Similar growth patterns, when P. abies seedlings with most abundant ECM colonisation showed reduced rates of height increment were observed in the study conducted on replanted forest clear-cut (Menkis et al 2010).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…One of the growth media most utilized for growing containerized plants is peat, used either alone or as a main component of peatbased growing mixtures (Landis et al 1990, Vaario et al 2009, Heiskanen 2013. Especially light low-humified Sphagnum peat has the required attributes (such as low pH, high cation exchange capacity, low inherent fertility, a proper balance of aeration and waterholding porosity) and provides reasonable growth conditions in the greenhouse (Landis et al 1990, Heiskanen 1993.…”
Section: Introductionmentioning
confidence: 99%
“…Rytter et al (2003) investigated the field performance of containerized seedlings of silver birch and Norway spruce and suggested that shoot length was of lesser importance to future growth than a high root/ shoot ratio, which is of known importance in the growth of other conifers. Furthermore, it has been reported that the production of new roots can rapidly alleviate the reduced growth of seedlings caused by transplant shock (Davis and Jacobs 2005) and improve nutrient uptake by supporting more ectomycorrhizal fungi (Vaario et al 2009). The fact that aspen seedlings have more roots in forest soil than in sandy soil (corresponding to higher root/shoot ratio) could also be explained by the higher amount of organic matter in the former.…”
Section: Discussionmentioning
confidence: 99%